STORE ATMOSPHERE ANALYSIS ON BUYING INTEREST AT BREGAS COFFEE SHOPS - Steven Arianto; Vishnuvardhana S. Soeprapto (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
Bregas Coffee, located at Jalan Pangeran Jayakarta, Complex 68, Block A, No.1, Central Jakarta. Bregas Coffee Shop has a deficient store atmosphere and has a relatively large number of visitors. The aim of this research is to analyze whether store atmosphere has an influence on buying interest. The research method used is a quantitative method, while the population in this research is consumers who have made purchases at the Bregas Coffee Shop. The sampling technique used is non- probability sampling. The results of the research itself show that the Store Atmosphere has a positive and significant effect on purchasing interest at the Bregas Coffee Shop. Thus, an increase in buying interest at the Bregas Coffee Shop can occur when the Store Atmosphere provided by the Bregas Coffee Shop increases.